Estudio de prefactibilidad para la instalación de una planta productora de pulpa congelada de açai (Euterpe oleracea) para exportar a Estados Unidos - Ayulo Gobelli, Mauricio Eduardo (2020)
The project will consist in the export of açai frozen pulp to the United States market. Açai frozen pulp has very high levels of antioxidants and large concentrations of proteins which gives it a competitive advantage over other products in the market. The project will be developed in the city of Tarapoto, San Martin since it has the ideal climate for planting and growing palm trees. The processing plant will be located next to the plantation to ensure the freshness of the fruit as this is the essential factor to prevail in the market. For this project, an investment of US$ 8,392,777 will be required for the implementation of a plantation of açai palm trees and the installation of a processing plant that can produce up to 3,878,280 kg of frozen pulp, an amount that can supply 10% of the US market demand. The field will have a plot of 201 hectares, which will feed the raw material to the industrial plant. Due to the fact that açai palms take 3 years to harvest their first fruits, the company will start receiving revenues from the year 2020 onwards. Therefore, in order to make the most efficient use of the capital, the project investment will be phased. It is proposed that the first capital contribution of shareholders (US$ 5,414,668) will be in the first year (2017), the bank will make two disbursements, the first disbursement (US$ 800,000) in year 2 (2018) and the second (US$ 1,516,322) in the year 3 (2019). The sum of these 3 contributions will be the Initial Investment (US$ 7,721,077); this will be used to purchase the fixed assets and also to cover the expenses of the first 3 years without income. In the 3rd year the shareholders will make a second contribution (US$ 671,700), this will prevent the equity from being negative and will also maintain a debt ratio (Liabilities / Equity) lower than 3.5 (requirements of the bank). 30% of the initial investment will be financed by COFIDE through its PROBID investment program and channeled through Agrobanco (intermediary). The debt to be repaid, which will have a partial grace period of 2 years, must be paid in 7 years with constant installments to an annual effective tax rate of 20%. The debt will begin to be paid starting the year 2020. The project will have a payback period of 8.18 years, an internal recovery rate of 23.37%, an NPV of US$ 11,942,395 and a cost benefit ratio of US$10.79. For each dollar that the shareholder invests, it will have a profit of US$ 10.79.